2020
DOI: 10.5296/jei.v6i2.17326
|View full text |Cite
|
Sign up to set email alerts
|

Is Technology in Our Classrooms? EFL Teachers’ Beliefs and Engagement with Technology in the Classroom

Abstract: This study aims to investigate the beliefs of Turkish EFL teachers about implementing digital technology in the classroom and the underlying factors which affect their beliefs. Quantitative research design was selected and online Beliefs Questionnaire was used for data collection. The participants of the study consisted of 563 Turkish in-service EFL teachers working at state schools, private schools or colleges in various parts of Turkey. Descriptive statistics and correlation analysis were performed to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…held positive views about the use of video technology in English teaching, which sustained the findings from the previous studies (e.g., Ding et al, 2019;Farrell, 2016;Hol & Aydın, 2020;O'Neal et al, 2017). Nevertheless, having positive beliefs about video did not necessarily reflect the teachers' classroom practices.…”
Section: Reading Literature Facilitysupporting
confidence: 78%
See 1 more Smart Citation
“…held positive views about the use of video technology in English teaching, which sustained the findings from the previous studies (e.g., Ding et al, 2019;Farrell, 2016;Hol & Aydın, 2020;O'Neal et al, 2017). Nevertheless, having positive beliefs about video did not necessarily reflect the teachers' classroom practices.…”
Section: Reading Literature Facilitysupporting
confidence: 78%
“…Early studies have pointed out that if a change in classroom practice is the intended outcome, addressing the change in teachers' beliefs about the use of the provided technology is crucial (e.g., Ottenbreit-Leftwich et al, 2010;Palak & Walls, 2009). In this regard, recent studies conducted among English language teachers have found several insights: 1) teachers' content-specific pedagogical beliefs can be different, which, in turn, results in the various ways of utilizing the same type of technological tools (Ding et al, 2019), 2) EFL teachers commonly share positive views on the use of digital technology, but gender, age, and teaching experience cannot alter teachers' beliefs (Hol & Aydın, 2020), and 3) despite having adequate knowledge of technology use in teaching, teachers may still be hesitant and unable to use technology in their classroom practices due to inadequate training, resources, and facilities (Nugroho & Mutiaraningrum, 2020).…”
Section: Teachers' Beliefsmentioning
confidence: 99%
“…The factor in the TAM model describing perceived usefulness was split into two factors, perceived usefulness for teachers and perceived usefulness for students, which was not reported previously. Previous studies about the TAM model and beliefs about technology use in education used only one perceived usefulness factor, despite the fact that in some studies (e.g., [4,16,39]), this factor included items describing both usefulness for students and usefulness for teachers. The convergent and discriminant validity of the scale were also established, indicating that separating perceived usefulness into two factors is reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…The use of technology is necessary, in the context of teacher professional development and for students, to engage and motivate teachers and students, improve their comprehension, and develop their technological skills [3]. The use of technology provides greater flexibility in teaching, allowing, for example, accounting for different types of intelligence and interests [4]. The COVID pandemic, which began worldwide in spring 2020, has brought this issue even more into focus.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the English language is currently the most common language of communication amongst people of different first languages in the field of business, commerce and the sciences as well as in academia. In the EFL context, the increasing relevance of the English language can also be recognized in the employment and education sectors [5] and in consideration of the relevance of the English language in the EFL context, new language policies have been introduced by the governments such as the Saudi government, which demands that all students both at the high and the intermediate school levels to compulsorily study the English language [6]. The English language has also become the mode of teaching in most Arab schools [7].…”
Section: Introductionmentioning
confidence: 99%